2013
DOI: 10.1017/s1368980013000864
|View full text |Cite
|
Sign up to set email alerts
|

The folate status of reproductive-aged women in a randomised trial of a folate-fortified oral contraceptive: dietary and blood assessments

Abstract: Objective: To assess the folate status of US women in a study of a folate-fortified oral contraceptive (OC) using the Short Folate Food Frequency Questionnaire and plasma and red blood cell (RBC) folate samples. Design: Sub-analysis from a multi-centre, randomised, double-blind, controlled contraceptive trial with assessments at baseline and 6 months. We calculated dietary folate equivalents (DFE) consumed and the proportion of participants meeting folate adequacy benchmarks. Setting: Eight centres in the USA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
(58 reference statements)
0
7
0
1
Order By: Relevance
“…Ultimately, five articles met the final inclusion criteria. [8][9][10][11][12] The five studies presented in this category are summarized in the Table. Bioequivalence studies Wiesinger et al 9 conducted a randomized, open-label, threeperiod, crossover study at a single centre in Germany to evaluate the bioequivalence of a new folate-supplemented oral contraceptive preparation (containing ethinyl estradiol, drospirenone, and levomefolate calcium) with its nonsupplemented counterpart (containing ethinyl estradiol and drospirenone) and levomefolate calcium (5-methyl-THF) separately. Within this intra-individual crossover design, each participant was randomized to a treatment sequence that included: Each treatment commenced between the third and sixth days of the participant's menstrual cycle, and each treatment was administered as a single dose orally, along with extensive dietary restrictions that were standardized across all participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, five articles met the final inclusion criteria. [8][9][10][11][12] The five studies presented in this category are summarized in the Table. Bioequivalence studies Wiesinger et al 9 conducted a randomized, open-label, threeperiod, crossover study at a single centre in Germany to evaluate the bioequivalence of a new folate-supplemented oral contraceptive preparation (containing ethinyl estradiol, drospirenone, and levomefolate calcium) with its nonsupplemented counterpart (containing ethinyl estradiol and drospirenone) and levomefolate calcium (5-methyl-THF) separately. Within this intra-individual crossover design, each participant was randomized to a treatment sequence that included: Each treatment commenced between the third and sixth days of the participant's menstrual cycle, and each treatment was administered as a single dose orally, along with extensive dietary restrictions that were standardized across all participants.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the event of an unplanned pregnancy it provides blood folate levels that are optimally protective against NTDs. 8,11 Even without pregnancy, it provides the appropriate daily folate dose for women to maintain good health.…”
Section: Target Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis and systematic review concluded "Because of the reduction in blood folate concentrations associated with the use of oral contraceptives, it is critical for women of childbearing age to continue folate supplementation during oral contraceptive use" [48]. In 2012, in recognition of this, an oral contraceptive fortified with folate was made available in some markets as a means of lowering the hazard of neural tube defects (NTDs) in females who might become pregnant during OC use or shortly after discontinuation [49,50]. Evidence also suggests that OCs might enhance the rate of progression of cervical dysplasia to cervical cancer, and folic acid may be able reverse or reduce the rate of progression of this dysplasia [51,52].…”
Section: Folic Acidmentioning
confidence: 99%
“…Целевая аудитория этих препаратов -наиболее нуждающиеся в фолиевой кислоте женщины детородного возраста, и данная стратегия имеет огромные преимущества в отличие от широкого применения диетического обогащения фолатами. Таким образом, в случае незапланированной беременности КОК с фолатами обеспечивает их оптимальный уровень для профилактики ДНТ [52]. Независимо от того, планирует женщина беременность или нет, препараты обеспечивают необходимой ежедневной дозой фолата для поддержания здоровья.…”
unclassified